1981
DOI: 10.1128/aem.41.1.51-59.1981
|View full text |Cite
|
Sign up to set email alerts
|

One-year survey of enteroviruses, adenoviruses, and reoviruses isolated from effluent at an activated-sludge purification plant

Abstract: were taken every 6 h to determine the effects of diurnal variation of flow on virus load. MATERIALS AND METHODS Sampling site. Sewage and effluent samples were collected from a modem activated-sludge treatment plant situated 35 km (22 miles) from the city of Melbourne. This plant processes 290 Ml of domestic and industrial wastewater per day, providing service for a domestic population of 980,000 and industrial biological oxygen demand equivalent to a population of 544,000 in the southeastern and eastern secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(56 citation statements)
references
References 13 publications
6
50
0
Order By: Relevance
“…That adenoviruses are naturally present in sewage in greater numbers than enteroviruses, has been shown true by the studies of both Irving and Smith (1981) and Krikelis et al (1985), and is confirmed by our results. Our finding that the average number of adenoviruses present in sewage concentrates, as measured by cytopathogenicity using the 293 cell line, was 94-fold greater than for the enteroviruses as determined by plaque assay, contrasts with the findings of the above investigators who have reported differences of approx.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…That adenoviruses are naturally present in sewage in greater numbers than enteroviruses, has been shown true by the studies of both Irving and Smith (1981) and Krikelis et al (1985), and is confirmed by our results. Our finding that the average number of adenoviruses present in sewage concentrates, as measured by cytopathogenicity using the 293 cell line, was 94-fold greater than for the enteroviruses as determined by plaque assay, contrasts with the findings of the above investigators who have reported differences of approx.…”
Section: Discussionsupporting
confidence: 91%
“…Thirdly, we believe that the large difference in the number of adenoviruses vs enteroviruses detected in the present study can also be attributed in part to our use of a cell line, 293, which is more sensitive for adenovirus detection than were those used in the studied by Irving and Smith (1981) and Krikelis et al (1985). Clearly, the utilization of guanidine as a media additive to suppress replication of indigenous enteroviruses was also a benefit in our being able to detect adenoviruses.…”
Section: Discussionmentioning
confidence: 77%
“…Enriquez et al (1995) concluded that enteric adenoviruses are more stable in tap water and wastewater than poliovirus. Irving and Smith (1981) reported that adenoviruses are more likely to survive conventional sewage treatment than enteroviruses. In addition, Hurst et al (1988) estimated that most adenoviruses detected in wastewater may be enteric adenoviruses.…”
Section: A Pcr Case Study For Environmental Virologymentioning
confidence: 99%
“…Adenoviruses have been found in wastewater samples in significant numbers in different geographic locations (Irving and Smith, 1981;Krikelis et al, 1985a, b;Hurst et al, 1988, Puig et al, 1994Greening et al, 2002;He and Jiang 2005). Girones et al (1995) presented data that showed the prevalence of adenoviruses in sewage samples.…”
Section: A Pcr Case Study For Environmental Virologymentioning
confidence: 99%
“…Salmonella Typhimurium is one of the most common enteric infections in New Zealand [reported incidence rates are 32AE2 cases per 100 000 persons (New Zealand Public Health Surveillance Report 2008)] and is also able to grow in the environment (Zaleski et al 2005;Sinton et al 2007). HAdVs are DNA viruses that cause a wide range of symptoms, are shed in large numbers in faeces and are frequently present at high levels in sewage (Irving and Smith 1981). HAdV may be useful as enteric virus indicators because of their prevalence and apparent environmental stability in environmental samples including wastewaters, sewage sludge and surface waters (Irving and Smith 1981;Enriquez et al 1995;Pina et al 1998).…”
Section: Introductionmentioning
confidence: 99%